Enhancing use of the cubic space of hose export containers in an agro-industrial company in Perú - Aradiel Abad, Cristhian Giancarlo; Dávila Vilchez, Diego Ángel; Gamboa Rojas, Tania Sthefany; Veliz Ponce, Gabriela Paola (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
This article describes the current situation of the export of hydraulic hoses in Peru, analyzes the main factors that increase the export cost and proposes a linear programming model to determine the type of container to use according to the exposed variables.